Policy Formulation of The Marine Governance in The Coastal Southern Lebak Regency Banten Province - Delly Maulana; Arif Nugroho (School of Postgraduate Studies, Diponegoro Univer, 2020)
This paper is aimed to explain the presence of marine potentials in the southern coastal area of Lebak Regency, Banten Province that have not been fully exploited. There are several potentials found in this Regency, the extensive coastline of approximately 91.42 km², and the marine resources and fisheries that could be developed. The potentials include not only fisheries and tourism but also mining. With such a high rate of development in the coastal area of Lebak Regency, it will certainly cause various problems in the region such as First, the degradation of coastal and marine ecosystems in Lebak Regency; Second, the increasing intensity of environmental pollution caused by mining and extraction activities; Third, the vulnerability to natural disasters (abrasion, tsunami, erosion, climate change, et cetera); Fourth, the occurrence of area utilization conflict; and Fifth, low productivity of biological marine resources utilization. The method used in this study was a qualitative research method with in-depth interviews, observations, and documentation. The results show that two issues become marine management problems in the southern coastal area of Lebak Regency, the first is environmental degradation, the second is space use conflicts, and the third is waste pollution due to organic and non-organic waste. Meanwhile, actor mapping shows that the government, in this case, the Regent as the authority in the area, has the power, influence, and interest to give input to the marine management of the Southern Coast of Lebak Regency so that it would not only increase the local revenue but also have a significant effect on the local communities, especially the fisher people and, and the environmental sustainability.ABSTRACTThis paper is aimed to explain the presence of marine potentials in the southern coastal area of Lebak Regency, Banten Province that have not been fully exploited. There are several potentials found in this Regency, the extensive coastline of approximately 91.42 km², and the marine resources and fisheries that could be developed. The potentials include not only fisheries and tourism but also mining. With such a high rate of development in the coastal area of Lebak Regency, it will certainly cause various problems in the region such as First, the degradation of coastal and marine ecosystems in Lebak Regency; Second, the increasing intensity of environmental pollution caused by mining and extraction activities; Third, the vulnerability to natural disasters (abrasion, tsunami, erosion, climate change, et cetera); Fourth, the occurrence of area utilization conflict; and Fifth, low productivity of biological marine resources utilization. The method used in this study was a qualitative research method with in-depth interviews, observations, and documentation. The results show that two issues become marine management problems in the southern coastal area of Lebak Regency, the first is environmental degradation, the second is space use conflicts, and the third is waste pollution due to organic and non-organic waste. Meanwhile, actor mapping shows that the government, in this case, the Regent as the authority in the area, has the power, influence, and interest to give input to the marine management of the Southern Coast of Lebak Regency so that it would not only increase the local revenue but also have a significant effect on the local communities, especially the fisher people and, and the environmental sustainability.